Systematic review of the effect of taping techniques on patellofemoral pain syndrome - Logan, Catherine (2017)
RESUMEN A checklist method was used to determine selection, performance, detection, and attrition bias for each article. A quality of evidence grading was then referenced using the validated PEDro database for RCTs. Three difference comparison groups were compared: tension taping and exercise versus placebo taping and exercise (group 1), placebo taping and exercise versus exercise alone (group 2), and tension taping and exercise versus taping alone (group 3). Five RCTs with 235 total patients with multiple intervention arms were included. Taping strategies included McConnell and Kinesiotaping. Visual analog scale (VAS) scores indicated improvement in all 3 comparison groups (group 1: 91 patients, 39% of total, mean VAS improvement 44.9 [tension taping + exercise] vs 66 [placebo taping + exercise]; group 2: 56 patients, 24% of total, mean VAS improvement 66 [placebo taping + exercise] vs 47.6 [exercise alone]; and group 3: 112 patients, 48% of total, mean VAS improvement 44.9 [tension taping + exercise] vs 14.1 [taping alone]).